Multi-driving-mode antibacterial hydrogel as well as preparation method and application thereof
By adopting the multi-drive method of antibacterial hydrogel preparation method, the composite of functional particles and other materials is used to solve the problem of degradation of antibacterial performance during deformation and driving, and the effect of improving antibacterial performance during deformation is achieved. .
Patent Information
- Application Number
- CN202411576256.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-06
AI Technical Summary
Existing hydrogel drivers will reduce their catalytic antibacterial properties during deformation and driving, or it will be difficult to affect catalytic antibacterial properties, resulting in weak catalytic antibacterial properties during application.
The multi-driven antibacterial hydrogel preparation method is adopted to form a composite antibacterial hydrogel by mixing functional particles, acrylamide, N,N'-methylenebisacrylamide and other materials evenly. The hydrogel can react to infrared light, sunlight, temperature changes, produce deformation and/or movement, and improve antibacterial properties during deformation.
During the deformation process of hydrogel, by increasing the contact area and exposing more reaction sites, catalytic antibacterial performance is significantly improved, and the dual controllability of driving mode and antibacterial performance is achieved.
Smart Images

Figure CN119431826A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of functional materials, and in particular to an antibacterial hydrogel with multiple driving modes and a preparation method and application thereof. Background Art
[0002] Light stimulation is a remote exogenous effect, and many functional designs and applications can utilize light. When photothermal materials are compounded in hydrogels, light can increase their temperature, which can then be used for light-driven deformation and photothermal antibacterial. There are many traditional photothermal materials compounded in hydrogels, such as organic substances such as polyaniline and polypyrrole, and inorganic substances including pure metal nanoparticles, metal compound nanoparticles, etc.
[0003] In recent years, bionic hydrogel actuators that imitate the various characteristics and movements of organisms have received widespread attention. By simulating the movement modes of animals and plants such as swimming, jumping, and crawling, hydrogels can be used in various engineering scenarios. Existing research on hydrogel actuators mainly focuses on the movement and deformation of hydrogels, for example, increasing the movement speed of hydrogels, enriching the bionic movement types of hydrogels, increasing the driving modes of hydrogels, and so on. However, the catalytic antibacterial properties of hydrogels may be reduced during the deformation and driving process, or the catalytic antibacterial properties may not be affected, resulting in the catalytic antibacterial properties of hydrogels being still weak when used. Therefore, how to further improve the antibacterial properties in the process of hydrogel deformation and driving is an issue worthy of special attention. Summary of the invention
[0004] One object of the present invention is to provide a method for preparing an antibacterial hydrogel with a multi-drive mode. The preparation method has mild reaction conditions and a short synthesis path. The prepared antibacterial hydrogel can respond to infrared light, sunlight, temperature changes, produce deformation and / or movement, and improve the antibacterial performance of the antibacterial hydrogel during the deformation process, and has wide application value.
[0005] The present invention is achieved through the following technical solutions:
[0006] A method for preparing an antibacterial hydrogel with multiple driving modes comprises the following steps:
[0007] The functional particles, acrylamide, and N,N'-methylenebisacrylamide are uniformly mixed to obtain a first layer of precursor solution;
[0008] N-isopropylacrylamide, polyethylene glycol, and N,N'-methylenebisacrylamide are uniformly mixed to obtain a second layer of precursor solution;
[0009] Tetramethylethylenediamine and potassium persulfate are added to the first layer precursor solution to obtain a first solution, and the first solution forms a first layer of antibacterial hydrogel after reaction; tetramethylethylenediamine and potassium persulfate are added to the second layer precursor solution to obtain a second solution, and the second solution forms a second layer of antibacterial hydrogel after reaction, and the second layer is connected to the first layer.
[0010] In this technical solution, the first layer of precursor solution is obtained by mixing functional particles, acrylamide, and N,N'-methylenebisacrylamide evenly, and the first layer of precursor solution is added with tetramethylethylenediamine and potassium persulfate to obtain a first solution, and the first solution is stirred and shaken to solidify and form the first layer of antibacterial hydrogel. The prepared first layer has the functional particles compounded in the first layer, that is, the PAM (polyacrylamide) gel layer.
[0011] In the present technical solution, similarly, a second layer of precursor solution is obtained by uniformly mixing N-isopropylacrylamide, polyethylene glycol, and N,N'-methylenebisacrylamide, and a second solution is obtained by adding tetramethylethylenediamine and potassium persulfate to the second layer of precursor solution, and the second solution is solidified and formed to obtain the second layer of antibacterial hydrogel after being stirred and shaken. The prepared second layer is a PNIPAM (poly (N-isopropylacrylamide)) gel layer, and the second layer and the first layer are connected to each other.
[0012] In this technical solution, the PAM of the first layer is not thermosensitive and will not produce obvious deformation under the action of light and temperature. The composite functional particles in the first layer can convert light into heat and transfer the heat to the second layer through the first layer. The PNIPAM of the second layer is a thermosensitive material. Therefore, after the temperature is raised to a temperature greater than the lowest eutectic temperature (LCST), the second layer will gradually shrink, driving the first layer to unfold, and the antibacterial hydrogel will bend to a certain extent compared to the initial state in this process; after the temperature is reduced to the lowest eutectic temperature (LCST), the second layer will gradually recover and drive the first layer to recover, and the antibacterial hydrogel will gradually return to its initial state in this process. In some embodiments, a specific driving mode can be achieved by cutting the antibacterial hydrogel into a specific shape, such as imitating the movement of an inchworm, grasping objects, and unfolding leaves.
[0013] In this technical solution, the functional particles can not only convert light into heat, but also use photocatalytic activity to catalytically degrade pollutants in water and achieve antibacterial properties. When the antibacterial hydrogel deforms and bends, the contraction of the second layer will drive the first layer to expand. In the process of completing specific actions and achieving bionic drive, the contact area between the first layer and the pollutants will gradually increase, and the functional particles in the first layer will be further dispersed, thereby exposing more reaction sites, thereby greatly improving the catalytic antibacterial performance.
[0014] In this technical solution, the functional particles can be selected from existing photothermal materials with catalytic antibacterial capabilities, such as organic substances such as polyaniline and polypyrrole, and inorganic substances such as metal nanoparticles, metal compound nanoparticles, etc. In some preferred embodiments, the functional particles can be Fe3O4 nanoparticles, which are a typical mineral with magnetic, photothermal and catalytic properties. They can not only achieve the above-mentioned photothermal and catalytic capabilities, but also respond to magnetic drive, further enriching the driving mode of the antibacterial hydrogel. In some preferred embodiments, the functional particles can also use improved Fe3O4 nanoparticles to further improve the catalytic performance of the antibacterial hydrogel.
[0015] In the present technical solution, the prepared antibacterial hydrogel can deform in response to light and heat, complete a specific movement mode, and then complete a specific function in a specific application scenario, such as using the crawling of a bionic inchworm to move to the area to be degraded, or by reducing the contact between the pollutants and the surface of the first layer when not deformed to protect the surface of the first layer; at the same time, during the driven deformation process, the surface of the first layer, that is, its contact surface with the pollutants, can be expanded, so that the functional particles are better dispersed in the first layer, exposing more reaction sites, so that the antibacterial hydrogel can greatly improve its antibacterial performance after deformation, and realize dual controllability of the driving mode and antibacterial performance.
[0016] As a preferred embodiment of the present invention, the functional particles are prepared by the following steps:
[0017] FeCl3, FeSO4 and ammonia water react to obtain Fe3O4 suspension;
[0018] The Fe3O4 suspension and the Cu(NO3)2 solution are uniformly mixed and then reacted with polyvinyl pyrrolidone and Na2S to obtain functional particles.
[0019] In this technical solution, FeCl3, FeSO4 and ammonia water react to obtain Fe3O4 suspension. Then, the Fe3O4 suspension is mixed with Cu(NO3)2 solution, and polyvinyl pyrrolidone (PVP) and Na2S solution are added to react to obtain functional particles. The functional particles are washed by magnetic separation, and the Fe3O4 / CuS suspension is collected and placed in a centrifuge tube and sealed for low-temperature storage for subsequent preparation of the first layer of precursor solution.
[0020] In this technical solution, the functional particles prepared are Fe3O4 / CuS particles, wherein CuS is adsorbed on Fe3O4, making the Fe3O4 / CuS particles have stronger photocatalytic activity than pure Fe3O4 particles. This is because the Fe3O4 / CuS particles generate ·OH and ·O 2-To catalyze the degradation of MB (methylene blue), and the migration and separation efficiency of photoinduced carriers play an important role in the photocatalytic reaction, and the photogenerated carriers are easy to migrate and transfer in Fe3O4 / CuS. Specifically, the band gap of Fe3O4 is 1.25ev, the band gap of CuS is 1.69ev, and the band gap of Fe3O4 / CuS is between the two, which is 1.61ev. According to the fine valence band spectrum mapping, the valence bands of Fe3O4, CuS and Fe3O4 / CuS were obtained, which are 0.99ev, -0.10ev and 0.66ev respectively. Conduction band potential = valence band potential + band gap, it can be seen that the conduction bands of CuS and Fe3O4 are 1.59ev and 2.23ev respectively. When illuminated with the assistance of H2O2, photogenerated electrons will transfer from CuS with a lower valence band potential (-0.10ev) to Fe3O4 with a higher potential (0.99ev), and photogenerated holes will transfer from Fe3O4 with a higher conduction band potential (2.23ev) to CuS with a lower potential (1.59ev), which promotes the transfer of electrons and reduces the recombination of electrons and holes. The separation and generation of electron-hole pairs can react with the surrounding O2, H2O and H2O2 to produce O 2- and OH. 2- and ·OH can react with MB and degrade it into small organic molecules, water and CO2.
[0021] At the same time, Fe3O4 / CuS particles also make the antibacterial hydrogel after adding H2O2. In addition to sterilization by photothermal effect, the antibacterial hydrogel can also catalyze H2O2 to produce ·OH and O under the irradiation of xenon light. 2- , causing oxidative damage to bacterial cell membranes and internal biomolecules, thereby effectively killing bacteria, so the antibacterial hydrogel has a broad-spectrum antibacterial property. Through antibacterial tests, it was found that the antibacterial rate of the antibacterial hydrogel against Escherichia coli and Staphylococcus aureus was close to 90%.
[0022] Furthermore, the functional particles are prepared by the following steps:
[0023] FeCl3 and FeSO4 are dissolved in deionized water, heated and stirred after dissolution, and then ammonia water is added. After stirring and reaction, a third solution is obtained, and the third solution is magnetically separated to obtain the Fe3O4 suspension; in some preferred embodiments, the reaction temperature is 80-100°C.
[0024] Subsequently, the Fe3O4 suspension and the Cu(NO3)2 solution are mixed, heated and stirred under an inert atmosphere, polyvinyl pyrrolidone and Na2S are added to obtain a fourth solution, and the fourth solution is subjected to magnetic separation to obtain functional particles. After the Fe3O4 suspension and the Cu(NO3)2 solution are mixed, an inert gas is introduced to remove dissolved oxygen in the solution, and the inert gas is preferably nitrogen or argon. In some preferred embodiments, the reaction temperature is 80 to 100°C.
[0025] Furthermore, the molar ratio of Fe3O4 and Cu(NO3)2 is 0.5-2. The molar ratio of Fe3O4 and Cu(NO3)2 determines the amount of CuS adsorbed on the surface of Fe3O4, affects the efficiency of electron transfer, and ultimately affects the catalytic efficiency of Fe3O4 / CuS particles after being compounded into antibacterial hydrogel. The inventor team found through experiments that when the molar ratio of Fe3O4 and Cu(NO3)2 is 0.5-2, the catalytic performance of the antibacterial hydrogel is better, and within this range, the degradation rate of the antibacterial hydrogel under light conditions increases with the increase of the molar ratio of Fe3O4 and Cu(NO3)2, showing a trend of first increasing and then decreasing. Therefore, in some preferred embodiments, the molar ratio of Fe3O4 and Cu(NO3)2 is 0.5-1, and further preferably, the molar ratio of Fe3O4 and Cu(NO3)2 is 1.
[0026] As a preferred embodiment of the functional particle concentration in the present invention, in the first layer precursor solution, the functional particle concentration is 5 to 30 mg / mL.
[0027] Fe3O4 / CuS particles are photothermal particles that can convert light energy into thermal energy. After being compounded into the first layer, the higher the concentration of Fe3O4 / CuS particles, the faster the heating rate of the first layer. Correspondingly, the faster the temperature of the first layer is transferred to the second layer, and the greater the deformation degree of the thermosensitive second layer. Therefore, when the concentration of Fe3O4 / CuS particles is less than or equal to 20 mg / mL, the deformation rate of the antibacterial hydrogel increases as the concentration of Fe3O4 / CuS particles increases. However, when the concentration of Fe3O4 / CuS particles increases further, the modulus of the first layer will also increase accordingly, so that the second layer needs to overcome greater resistance when shrinking, resulting in a decrease in the deformation rate of the antibacterial hydrogel. Therefore, in the present technical solution, the concentration of Fe3O4 / CuS particles is preferably 5-30 mg / mL, and further preferably, the Fe3O4 / CuS particles are 20-30 mg / mL.
[0028] As another preferred embodiment of the present invention, the second solution is first poured into the mold to react to form the second layer, and then the first solution is poured into the mold to react to form the first layer connected to the second layer.
[0029] In this technical solution, the prepared second solution is first poured into the mold for reaction to obtain the second layer, and then the first solution is poured into the mold to form the first layer on top of the second layer. During the process of pouring the first solution into the mold to react and form the first layer, the Fe3O4 / CuS particles in the first solution will move downward under the action of gravity, so that the Fe3O4 / CuS particles in the final antibacterial hydrogel are more concentrated near the interface between the first layer and the second layer.
[0030] The concentration of Fe3O4 / CuS particles at the interface between the first layer and the second layer enables the heat generated by the Fe3O4 / CuS particles to be directly transferred to the second layer, reducing heat loss, improving heat transfer efficiency, and effectively increasing the heating rate of the second layer. In addition, since the particles are close to the interface, there are fewer particles on the surface of the first layer, so when the second layer shrinks due to heat, the outer surface of the first layer is more likely to open, the antibacterial hydrogel is more likely to deform, and has a larger contact area, exposing more reaction sites, thereby improving the antibacterial properties of the antibacterial hydrogel.
[0031] In one or more embodiments, the molds used are two glass sheets and the middle mold is composed of 0.5 mm thick silicone. The double-layer antibacterial hydrogel obtained can be used after being soaked in water to remove unreacted monomers.
[0032] In some preferred embodiments, after tetramethylethylenediamine is added to the first layer precursor solution or the second layer precursor solution, potassium persulfate is added and stirred evenly before pouring into the mold for forming. Specifically, after the first layer precursor solution and the second layer precursor solution are prepared, tetramethylethylenediamine is first added to the first layer precursor solution or the second layer precursor solution for standby use, and before pouring into the mold, potassium persulfate is added to the solution, and after shaking, it is directly poured into the mold for forming.
[0033] Another object of the present invention is to provide an antibacterial hydrogel with multiple driving modes, which is prepared by using any of the methods for preparing an antibacterial hydrogel with multiple driving modes described above, wherein the antibacterial hydrogel comprises a first layer and a second layer connected to each other, and the first layer contains the functional particles.
[0034] Preferably, the concentration of the functional particles gradually increases along a direction from a side of the first layer away from the second layer to an interface between the first layer and the second layer.
[0035] The present invention also provides an application of any of the aforementioned multi-drive antibacterial hydrogels, wherein the antibacterial hydrogel is used to deform under the influence of light and temperature, and expose more reaction sites through deformation, thereby improving the catalytic antibacterial performance.
[0036] Furthermore, two sheets of antibacterial hydrogel are fixed on a substrate, and the first layers of the two sheets of antibacterial hydrogel are attached to each other. After the two sheets of antibacterial hydrogel are placed in a target area, the two sheets of antibacterial hydrogel are bent by light and / or temperature changes to degrade pollutants in the target area. In this technical solution, the two sheets of antibacterial hydrogel are made into expandable leaves. Through experiments, it is found that the leaves can be expanded under light and catalytically degrade methylene blue pollutants, and have better photocatalytic performance than non-expandable leaves.
[0037] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0038] 1. The antibacterial hydrogel prepared by the present invention can respond to light and heat to produce deformation, complete a specific movement mode, and then complete a specific function in a specific application scenario. At the same time, during the driving deformation process, the contact surface between the antibacterial hydrogel and the pollutant can be expanded, so that the functional particles are better dispersed in the first layer, exposing more reaction sites, so that the antibacterial hydrogel can greatly improve its antibacterial performance after deformation, and realize dual controllability of driving mode and antibacterial performance;
[0039] 2. The present invention uses Fe3O4 / CuS particles as functional particles in the first layer. The addition of Fe3O4 / CuS particles enables the antibacterial hydrogel to have multiple functions such as photothermal, catalytic, magnetic response, and antibacterial. At the same time, Fe3O4 / CuS particles can promote the transfer of electrons and have stronger photocatalytic activity than pure Fe3O4 particles, so that the antibacterial hydrogel has a broad-spectrum antibacterial property.
[0040] 3. The present invention arranges the functional particles near the interface between the first layer and the second layer, which not only effectively improves the heating rate of the second layer, but also makes the outer surface of the first layer easier to open, so that the antibacterial hydrogel is easier to deform, has a larger contact area, and exposes more reaction sites, thereby improving the antibacterial performance of the antibacterial hydrogel;
[0041] 4. The present invention sets the concentration of the functional particles to 5-30 mg / mL, so that the antibacterial hydrogel not only has a faster heating rate, but also has a smaller resistance to overcome the increase in modulus when deforming, which is beneficial to improving the deformation rate of the antibacterial hydrogel;
[0042] 5. The present invention can further improve the catalytic performance of the antibacterial hydrogel by determining the molar ratio of Fe3O4 and Cu(NO3)2 to be 0.5-2. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] The drawings described herein are used to provide a further understanding of the embodiments of the present invention, constitute a part of this application, and do not constitute a limitation of the embodiments of the present invention. In the drawings:
[0044] Figure 1 It is a flowchart of the preparation method in a specific embodiment of the present invention;
[0045] Figure 2 The degradation rates of methylene blue catalyzed by Fe3O4, Fe3O4 / CuS-0.5, Fe3O4 / CuS-1, Fe3O4 / CuS-2 and pure H2O2 in the specific embodiments of the present invention under light conditions and dark conditions are shown;
[0046] Figure 3 The bending angles of the antibacterial hydrogels under light in the specific embodiments of the present invention are shown ( Figure 3 a) Bending rate ( Figure 3 b), and the bending photos of the antibacterial hydrogel FeCu-20 within one minute ( Figure 3 c);
[0047] Figure 4 The hysteresis loop of the antibacterial hydrogel in a specific embodiment of the present invention is shown;
[0048] Figure 5 The antibacterial performance of the antibacterial hydrogel against Escherichia coli in a specific embodiment of the present invention is shown. Figure 5 a shows the red dead bacteria and green live bacteria in each experimental group. Figure 5 b is the antibacterial rate, Figure 5 c is a photo of bacterial residues;
[0049] Figure 6 The antibacterial performance of the antibacterial hydrogel against Staphylococcus aureus in a specific embodiment of the present invention is shown. Figure 6 a shows the red dead bacteria and green live bacteria in each experimental group. Figure 6 b is the antibacterial rate, Figure 6 c is a photo of bacterial residues;
[0050] Figure 7 The antibacterial hydrogel in a specific embodiment of the present invention is shown to be driven by near-infrared light to perform inchworm-like movement;
[0051] Figure 8 It shows that the antibacterial hydrogel in a specific embodiment of the present invention can realize object grabbing, moving and releasing in containers with different water temperatures;
[0052] Fig. 9 It shows that the antibacterial hydrogel in a specific embodiment of the present invention moves driven by magnetic force;
[0053] Fig.10 The graph shows the efficacy of the antibacterial hydrogel in a specific embodiment of the present invention in mimicking the degradation of methylene blue by a leaf under xenon lamp irradiation ( Fig.10 a) Methylene blue degradation curve ( Fig.10 b), Fig.10c and Fig.10 d are the degradation photos of the unfoldable PAM-FeCu / PNIPAM leaf and the non-expandable PAM-FeCu / PAM bionic leaf within 60 minutes. DETAILED DESCRIPTION
[0054] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments and drawings. The exemplary embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.
[0055] All raw materials of the present invention are not particularly limited to their sources, and can be purchased on the market or prepared according to conventional methods well known to those skilled in the art. All raw materials of the present invention are not particularly limited to their purity, and the present invention preferably adopts analytically pure or conventional purity requirements in the field of functional materials. All raw materials of the present invention, their brands and abbreviations belong to conventional brands and abbreviations in this field, and each brand and abbreviation is clear and definite in the field of its related use. Those skilled in the art can purchase from commercial or prepare by conventional methods according to the brand, abbreviation and corresponding use.
[0056] 1. Preparation of hydrogel
[0057] [Example 1]
[0058] 1) Preparation of Fe3O4 particles: 2.43 g of FeCl3·6H2O, 1.67 g of FeSO4·7H2O, and 90 mL of deionized water were poured into a three-necked flask and stirred at 300 r / min for 30 min in a 90°C oil bath; then, 30 mL of ammonia water was added to react for 150 min, and finally the particles were magnetically separated and washed several times to obtain a Fe3O4 suspension.
[0059] 2) Preparation of Fe3O4 / CuS suspension: 1 mL of Fe3O4 suspension containing 0.01 mol and 99 mL of Cu(NO3)2·3H2O solution containing 0.01 mol were added to a three-necked flask, and argon was introduced for 10 min. The reaction system was stirred at 300 r / min in an oil bath at 90°C for 60 min. Then, 10 mL of 100 mg PVP and 10 mL of Na2S solution were added to the three-necked flask, and the reaction was continued for 150 min to obtain composite particles. The composite particles were magnetically separated and washed, and the Fe3O4 / CuS suspension was collected and put into a centrifuge tube, sealed and stored at low temperature. The composite particles were magnetically separated and washed, and the Fe3O4 / CuS suspension was collected and put into a centrifuge tube, sealed and stored at low temperature. The molar ratio of Fe3O4 and Cu(NO3)2 was 1, recorded as Fe3O4 / CuS-1.
[0060] 3) Preparation of hydrogel: 120 mg of AM (acrylamide), 500 μL of Fe3O4 / CuS suspension Fe3O4 / CuS-1 (40 mg / mL), 100 μL of BIS (N,N'-methylenebisacrylamide) (10 mg / mL), and 400 μL of deionized water were added to a 5 ml glass bottle and homogenized by ultrasonication as the first layer of PAM-Fe3O4 / CuS precursor solution, wherein the concentration of Fe3O4 / CuS was 20 mg / mL;
[0061] 120 mg NIPAM (N-isopropylacrylamide), 120 mg PEG, 100 μL BIS (10 mg / mL), and 900 μL deionized water were added to a 5 ml glass bottle and ultrasonically homogenized to form the second layer PNIPAM precursor solution;
[0062] Add 2 μL of TEMED (tetramethylethylenediamine) to the second layer precursor solution, then add 45 μL of KPS (potassium persulfate) solution (50 mg / mL), and then ultrasonicate in ice water for 2 minutes and quickly pour into the mold, wherein the mold includes a middle mold with a thickness of 0.5 mm and upper and lower openings, and two glass sheets for sealing the upper and lower openings of the mold, and react at room temperature for 1 hour;
[0063] After the reaction, the upper glass sheet of the mold was removed, and a 0.5 mm thick silicone mold was superimposed; 2 μL of TEMED was added to the first layer of PAM-Fe3O4 / CuS precursor solution, and 30 μL of KPS solution (50 mg / mL) was added after ultrasonic homogenization. After shaking, the solution was poured into the superimposed silicone mold, covered with a glass sheet, and placed in a 4°C refrigerator for reaction for 12 hours to obtain an antibacterial hydrogel. Since the concentration of the Fe3O4 / CuS suspension in the hydrogel was 20 mg / mL, it was recorded as hydrogel FeCu-20.
[0064] [Example 2]
[0065] The preparation process of the hydrogel in this embodiment is similar to that in Example 1, except that in step 3) of preparing the hydrogel in this embodiment, the amount of the Fe3O4 / CuS suspension added is adjusted so that the concentration of the Fe3O4 / CuS suspension in the prepared hydrogel is 5 mg / mL, and the hydrogel is recorded as FeCu-5.
[0066] [Example 3]
[0067] The preparation process of the hydrogel in this embodiment is similar to that in Example 1, except that, in step 3) of preparing the hydrogel in this embodiment, the amount of Fe3O4 / CuS suspension added is adjusted so that the concentration of Fe3O4 / CuS suspension in the prepared first layer precursor solution is 10 mg / mL, and the hydrogel is recorded as FeCu-10.
[0068] [Example 4]
[0069] The preparation process of the hydrogel in this embodiment is similar to that in Example 1, except that, in step 3) of preparing the hydrogel in this embodiment, the amount of Fe3O4 / CuS suspension added is adjusted so that the concentration of Fe3O4 / CuS suspension in the prepared first layer precursor solution is 30 mg / mL, and the hydrogel is recorded as FeCu-30.
[0070] [Example 5]
[0071] The preparation process of the hydrogel in this embodiment is similar to that in Example 1, except that, in step 2) of preparing the Fe3O4 / CuS suspension in this embodiment, 1 mL of a Fe3O4 suspension containing 0.005 mol is added to obtain a Fe3O4 / CuS suspension having a molar ratio of Fe3O4 to Cu(NO3)2 of 0.5, which is recorded as Fe3O4 / CuS-0.5, and the obtained hydrogel is recorded as FeCu-20-0.5.
[0072] [Example 6]
[0073] The preparation process of the hydrogel in this embodiment is similar to that in Example 1, except that, in step 2) of preparing the Fe3O4 / CuS suspension in this embodiment, 1 mL of a Fe3O4 suspension containing 0.02 mol is added to obtain a Fe3O4 / CuS suspension with a molar ratio of Fe3O4 to Cu(NO3)2 of 2, which is recorded as Fe3O4 / CuS-2, and the obtained hydrogel is recorded as FeCu-20-2.
[0074] [Comparative Example]
[0075] 120 mg of AM, 500 μL of Fe3O4 / CuS suspension (40 mg / mL), 100 μL of BIS (10 mg / mL), and 400 μL of deionized water were added to a 5 ml glass bottle and homogenized by ultrasonication as the first layer of PAM-Fe3O4 / CuS precursor solution, wherein the concentration of Fe3O4 / CuS was 20 mg / mL;
[0076] 120 mg of AM, 100 μL of BIS (10 mg / mL) and 900 μL of deionized water were added to a 5 mL glass bottle and homogenized by ultrasonication as the second layer PAM precursor solution;
[0077] Add 2 μL of TEMED to the second layer of PAM precursor solution, then add 45 μL of KPS solution (50 mg / mL), shake and quickly pour into the mold, and react at room temperature for 1 h;
[0078] After the reaction, the upper glass sheet of the mold was removed, and a 0.5 mm thick silicone mold was superimposed. Then, 2 μL of TEMED was added to the first layer of PAM-Fe3O4 / CuS precursor solution, and 30 μL of KPS solution (50 mg / mL) was added after ultrasonic homogenization. After ultrasonication in ice water for 2 min, the solution was poured into the superimposed silicone mold, covered with a glass sheet, and placed in a 4°C refrigerator for reaction for 12 h to obtain an antibacterial hydrogel, recorded as PAM-FeCuPAM.
[0079] 2. Performance test of hydrogel
[0080] [Example 8]
[0081] In this example, the catalytic performance of Fe3O4 / CuS particles was tested.
[0082] Specifically, 3 mg of the test agent was added to 10 mL of 10 mg / L MB solution, stirred for 30 min in the dark, then 50 μL of H2O2 was added, and then irradiated under a xenon lamp (0.5W) for 60 min. During illumination, 1 mL of liquid was taken from the solution every ten minutes, and 200 μL of supernatant was added to a 96-well plate after high-speed centrifugation, and its absorbance at a wavelength of 664 nm was tested using an ELISA instrument. Among them, the test agents include Fe3O4, H2O2, Fe3O4 / CuS-0.5, Fe3O4 / CuS-1 and Fe3O4 / CuS-2.
[0083] The experimental results are as follows Figure 2 As shown, Figure 2 The degradation rates of methylene blue catalyzed by Fe3O4, Fe3O4 / CuS-0.5, Fe3O4 / CuS-1, Fe3O4 / CuS-2 and pure H2O2 under light and dark conditions are shown. It can be seen that the degradation rates of all light groups are greater than those of the corresponding dark groups. The degradation rates of Fe3O4 / CuS particles of different concentrations under light conditions are significantly improved, and Fe3O4 / CuS particles have a significantly higher degradation rate than Fe3O4 / CuS particles. 4 / CuS-1 has the highest degradation rate and the best catalytic effect under both light and dark conditions.
[0084] [Example 9]
[0085] In this example, the bending ability of each hydrogel under the action of light was tested.
[0086] Specifically, the hydrogels FeCu-20, FeCu-5, FeCu-10, and FeCu-30 of Examples 1 to 4 and the double-layer hydrogel actuators containing different particle contents were cut into a size of 2×10 mm, one end of which was fixed, and the bending angle was tested by near-infrared irradiation for 60 seconds, and recorded with a mobile phone.
[0087] The experimental results are as follows Figure 3 a and Figure 3 As shown in Figure 2, each hydrogel in Examples 1-4 can bend at a certain angle under illumination. This is because Fe3O4 / CuS is a functional particle that can convert light energy into heat energy. After the heat energy generated by Fe3O4 / CuS is transferred to the second layer (PNIPAM layer) through the first layer (the layer where Fe3O4 / CuS is located), the second layer shrinks as the temperature rises, while the first layer hardly deforms, so the entire hydrogel bends.
[0088] like Figure 3 a and Figure 3 As shown in Figure b, when the concentration of Fe3O4 / CuS suspension in the hydrogel is less than 20 mg / mL, the greater the concentration of Fe3O4 / CuS, the faster the hydrogel heats up, and the faster its deformation and bending speed. The deformation rate of hydrogel FeCu-20 in one minute reaches nearly 65°. However, as the concentration of Fe3O4 / CuS further increases, the deformation rate decreases. This may be because after the concentration of Fe3O4 / CuS increases, the modulus of the first layer, that is, the PAM layer, is larger, and the force that the second layer needs to overcome during deformation increases accordingly, which is not conducive to improving the overall bending speed of the hydrogel.
[0089] Figure 3 c shows the bending of FeCu-20 hydrogel at 0, 20, 40, and 60 seconds.
[0090] [Example 10]
[0091] In this example, magnetic tests were performed on the hydrogel.
[0092] Specifically, the hysteresis loop of the dried hydrogel FeCu-20 was tested using a vibrating sample magnetometer. Figure 4 As shown, the hydrogel actuator has paramagnetism, and its saturation magnetization is 6.2 meu / g. The magnetism of the hydrogel comes from the Fe3O4 / CuS composite particles.
[0093] [Example 11]
[0094] In this embodiment, the hydrogel was subjected to antibacterial tests on Escherichia coli and Staphylococcus aureus. The operating steps of the two antibacterial tests were the same.
[0095] Specifically, the concentration of the bacterial solution used in the antibacterial test was 10 6CFU / mL. Add 1mL of bacterial solution to a 24-well plate as the control group. Add 40μL of 10mmol / L H2O2 to 1mL of bacterial solution as the H2O2 group. Place a 10×10mm PAM disc in a well plate, and drip 100μL of bacterial solution on the surface as the PAM group. Place a 10×10mm hydrogel FeCu-20 disc in a well plate, and drip 100μL of bacterial solution on the surface as the PAM-FeCu group. Place a 10×10mm hydrogel FeCu-20 disc in a well plate, and drip 100μL of bacterial solution containing the same substance as the H2O2 group on the surface as the PAM-FeCu-H2O2 group.
[0096] The antibacterial time for all antibacterial groups was 10 minutes. Five more groups were added under the same conditions and irradiated with xenon light for 10 minutes as the illumination group. After that, the bacterial solution of the 10 groups after antibacterial treatment was diluted 1000 times. Take 200μL of the diluted bacterial solution and evenly apply it on the plate.
[0097] The experimental results are as follows Figure 5 As shown, Figure 5 The plate images of the control group, PAM group, H2O2 group, PAM-FeCu group and PAM-FeCu-H2O2 group after treating Escherichia coli under xenon light illumination (+light) and non-illumination (-light) are shown ( Figure 5 c) and the corresponding antibacterial rate ( Figure 5 b). It can be seen that after 10 minutes of treatment without illumination, the number of E. coli in all groups did not change significantly. However, some E. coli died in all groups after xenon light illumination, which may be because the xenon light source contains ultraviolet light bands, which can kill some bacteria. After illumination, the antibacterial performance of the PAM-FeCu-H2O2 group was the best, with an antibacterial rate of 90.3%, and the antibacterial rate of the PAM-FeCu group was 82.8%, while the antibacterial rates of the other groups were all less than 50%.
[0098] Figure 6 The antibacterial properties of the five experimental groups under xenon light illumination (+light) and non-light (-light) were shown. Similarly, after 10 minutes of non-light treatment, there was no significant change in the number of Staphylococcus aureus in all groups. However, some Staphylococcus aureus died in all groups after xenon light illumination. After illumination, the PAM-FeCu-H2O2 group had the best antibacterial performance, with an antibacterial rate of 88.3%, the PAM-FeCu group had an antibacterial rate of 74.6%, and the antibacterial rates of the remaining groups were all less than 30%.
[0099] 3. Driving of Hydrogel
[0100] [Example 12]
[0101] This embodiment conducts a near-infrared light driving test. After the hydrogel is cut into long strips, the first layer of the hydrogel is placed on the top and the second layer is placed on the bottom. Figure 7 On the sawtooth base shown, one side of the sawtooth of the sawtooth base is a vertical surface, and the other side is an inclined surface facing the upper left direction. Of course, depending on the direction of the desired movement, the inclined surface of the sawtooth can also face the upper right direction.
[0102] When near-infrared light is irradiated on the middle area of the hydrogel (laser on), the first layer generates heat due to the photothermal effect and transfers it to the second layer, which shrinks due to the heat. Figure 7 As shown, the hydrogel bends similar to the body of an inchworm. During the contraction process, due to the design of the sawtooth, the friction force on the vertical surface of the sawtooth is greater than the friction force on the inclined surface. Therefore, when the hydrogel contracts upward, its left end will be anchored on the sawtooth, similar to the head of the inchworm, and the right end of the hydrogel will move to the left, similar to the tail of the inchworm.
[0103] When the near-infrared light source is removed, the temperature of the hydrogel will gradually drop, and it will gradually absorb water and expand. At this time, the right end of the hydrogel will be anchored on the sawtooth, and the left end will continue to move to the left, completing the crawling of the inchworm. Thus, the inchworm bionic drive is completed based on infrared light.
[0104] [Example 13]
[0105] This example conducts a temperature-driven test. The hydrogel is cut into a cross-shaped claw containing four long claws, each claw being 13 mm long and 5 mm wide. Figure 8 As shown, in a beaker at a temperature of 20°C (ambient temperature is lower than the minimum eutectic temperature), the hydrogel gripper is in an open state. When it is placed in a beaker at a temperature of 50°C (ambient temperature is higher than the minimum eutectic temperature), the hydrogel shrinks based on the same principle as mentioned above, and then enters a contracted state and grabs the object in the beaker. After the hydrogel gripper is placed in a beaker at a temperature of 20°C again, the hydrogel changes from a contracted state to an open state, releasing the grasped object. Therefore, by adjusting the temperature, hydrogel can be used to grasp and release objects.
[0106] [Example 14]
[0107] In Example 10, the hysteresis loop test verified that the hydrogel had paramagnetism. Therefore, in this example, the hydrogel prepared by driving a magnet was Fig. 9 Specifically, the hydrogel actuator is cut into small square pieces and placed in the maze, and magnets are used to guide its movement, and finally it walks out of the "maze".
[0108] [Example 15]
[0109] The FeCu-20 hydrogel prepared in Example 1 is recorded as PAM-FeCu / PNIPAM, and the comparative example is PAM-FeCuPAM. PAM-FeCu / PNIPAM and PAM-FeCuPAM are made into Fig.10 The bionic leaf structure shown in a, in which the side of the hydrogel containing Fe3O4 / CuS particles is arranged facing each other. Under the irradiation of a xenon lamp as simulated sunlight, the MB solution can be heated by thermal radiation. When the temperature exceeds the minimum eutectic temperature, the second layer of PAM-FeCu / PNIPAM will shrink, showing the morphology of two "leaves" open, while the PAM-FeCuPAM in the comparative example will not change significantly with the temperature because the morphology of the second layer will not change significantly. Therefore, the two "leaves" always remain closed.
[0110] It has been confirmed in the previous examples that Fe3O4 / CuS particles have catalytic properties and can photocatalytically degrade MB solution under light with the assistance of H2O2. Therefore, the hydrogel actuator containing Fe3O4 / CuS particles can also photocatalytically degrade MB solution under light. Fig.10 b to Fig.10 As shown in Figure d, with the increase of illumination time, MB is gradually degraded. At the same time, the PAM-FeCu / PNIPAM bionic leaf gradually changes from closed to unfolded, while the PAM-FeCu / PAM leaf cannot unfold. At the same time, the degradation rate of MB under illumination by the PAM-FeCu / PNIPAM bionic leaf is faster than that of the PAM-FeCu / PAM bionic leaf, the residual concentration of methylene blue is lower, and the solution color is lighter. After 60 minutes of illumination, the degradation rates of methylene blue by the PAM-FeCu / PNIPAM and PAM-FeCu / PAM bionic leaves are 89.1% and 36.5%, respectively. This is because the PAM-FeCu / PNIPAM bionic leaf can gradually unfold under illumination. After unfolding, the first layer on the inner side of the leaf can not only contact MB more fully, but also make more use of light energy. Therefore, compared with the PAM-FeCu / PAM bionic leaf that cannot unfold, the PAM-FeCu / PNIPAM leaf can degrade MB more efficiently under illumination.
[0111] It can be seen that the antibacterial hydrogel designed in the present invention not only has a variety of driving modes and can adapt to different application scenarios, but also during the driving process, the deformation of the hydrogel can greatly enhance the antibacterial ability of the antibacterial hydrogel by increasing the contact area and light-collecting area and exposing more reaction sites, thereby achieving an effective combination of driving ability and antibacterial performance.
[0112] The terms “first”, “second”, etc. (eg, first solution, second solution, etc.) used herein are used only to distinguish corresponding components for the sake of clarity of description and are not intended to limit any order or emphasize importance.
[0113] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing an antibacterial hydrogel with multiple driving modes, characterized in that: The following steps are involved: The functional particles, acrylamide, and N,N'-methylenebisacrylamide are uniformly mixed to obtain a first layer of precursor solution; N-isopropylacrylamide, polyethylene glycol, and N,N'-methylenebisacrylamide are uniformly mixed to obtain a second layer of precursor solution; Tetramethylethylenediamine and potassium persulfate are added to the first layer precursor solution to obtain a first solution, and the first solution forms a first layer of antibacterial hydrogel after reaction; tetramethylethylenediamine and potassium persulfate are added to the second layer precursor solution to obtain a second solution, and the second solution forms a second layer of antibacterial hydrogel after reaction, and the second layer is connected to the first layer.
2. The method for preparing a multi-drive antibacterial hydrogel according to claim 1, characterized in that: The functional particles are prepared by the following steps: FeCl3, FeSO4 and ammonia water react to obtain Fe3O4 suspension; The Fe3O4 suspension and the Cu(NO3)2 solution are uniformly mixed and then reacted with polyvinyl pyrrolidone and Na2S to obtain functional particles.
3. The method for preparing a multi-drive antibacterial hydrogel according to claim 2, characterized in that: The functional particles are prepared by the following steps: FeCl3 and FeSO4 are dissolved in deionized water, heated and stirred after dissolution, and then ammonia water is added, stirred and reacted to obtain a third solution, and the third solution is magnetically separated to obtain the Fe3O4 suspension; After the Fe3O4 suspension and the Cu(NO3)2 solution are mixed, they are heated and stirred under an inert atmosphere, polyvinyl pyrrolidone and Na2S are added to obtain a fourth solution, and the fourth solution is subjected to magnetic separation to obtain functional particles.
4. The method for preparing a multi-drive antibacterial hydrogel according to claim 2 or 3, characterized in that: The molar ratio of Fe3O4 and Cu(NO3)2 is 0.5-2.
5. The method for preparing a multi-drive antibacterial hydrogel according to claim 2 or 3, characterized in that: In the first layer of precursor solution, the concentration of the functional particles is 5 to 30 mg / mL.
6. The method for preparing a multi-actuation antibacterial hydrogel according to claim 1, characterized in that: First, the second solution is poured into the mold to react and form a second layer, and then the first solution is poured into the mold to react and form a first layer connected to the second layer.
7. An antibacterial hydrogel with multiple driving modes, characterized in that: The antibacterial hydrogel is prepared by the method for preparing a multi-drive antibacterial hydrogel according to any one of claims 1 to 6, wherein the antibacterial hydrogel comprises a first layer and a second layer connected to each other, and the first layer contains the functional particles.
8. The multi-actuation antibacterial hydrogel according to claim 7, characterized in that: The concentration of the functional particles gradually increases along a direction from a surface of the first layer away from the second layer to an interface between the first layer and the second layer.
9. An application of an antibacterial hydrogel with multiple driving modes, characterized in that: The antibacterial hydrogel according to claim 7 or 8 is used, wherein the antibacterial hydrogel is used to deform under the influence of light and temperature, and expose more reaction sites through deformation, thereby improving the catalytic antibacterial performance.
10. The use of the multi-actuation antibacterial hydrogel according to claim 9, characterized in that: Two sheets of antibacterial hydrogel are fixed on a substrate, and the first layers of the two sheets of antibacterial hydrogel are attached to each other. After the two sheets of antibacterial hydrogel are placed in a target area, the two sheets of antibacterial hydrogel are bent by light and / or temperature changes to degrade pollutants in the target area.
Citation Information
Patent Citations
Method for preparing asymmetric-structure hydrogel in one step by means of difference in viscosity, product of method and application of product
CN110229286A
Nano-enzyme composite material, portable sensing platform based on nano-enzyme hydrogel and application of portable sensing platform in detection of heavy metal ions
CN116351439A